التربية الإسلامية في المعاهد السلفية بأندونيسيا (دراسة تحليلية لمنهاج وطرق تدريس اللغة العربية والدين الاسلامي في المعاهد السلفية) - Abdul Aziz (LISANIYAT, 2010)
In the history of Islamization in Indonesia, Pesantren (boarding school) has a real central role. even some considered that the establishment of Pesantren  as an Islamic educational institution in conjunction with the arrival and spread of Islam in Indonesia. Establishment of Pesantren was Walisongo's contribution in which Maulana Malik Ibrahim as an elder of the nine religious leaders.From some existing types of Pesantren, this paper will elaborate the study about Pesantren which only teach religious sciences in the madrasah diniyah, such as Salafi pesantren Langitan Tuban, pesantren Hidayatul Mubtadiin Lirboyo Kediri, Pasuruan Sidogiri, etc.In case of Arabic language teaching methods, pesantren uses a certain method known as iki-iku . It is a method of reading the kitab kuning- a term to the classical Arabic books by the scholars' Salaf-using symbols nahwu (Grammar) and translated into classical Javanese. This method is intended that students be able to understand and study the texts in Arabic, whether it is in the Qur'an, Hadith, and another Arabic text.The method has the advantage of teaching the Arabic language (nahwu) and religion at the same time. Nevertheless, translations into classical Javanese language has a problem because this method requires the improvement or innovation to facilitate students in learning the language and religion and apply it in people's lives, so the method iki iku remains the alternative method.           In other hand, religious knowledge stipulated in the classical books needs to be supplemented and replaced by more recent books. Because the books are currently used in, written over a very long time, so that the content was less contextual with community issues at the moment. It was contrary to the principle of Walisongo, who was always sensitive to the needs of the community.Keywords: Islamic education, iki iku method, pesantren salaf